Quality of Life and Psychological Well-being in Children and Adolescents with Disorders of Sex Development - Birsen Şentürk Pilan; Burcu Özbaran; Didem Çelik; Tuğçe Özcan; Samim Özen; Damla Gökşen; İbrahim Ulman; Ali Avanoğlu; Sibel Tiryaki; Hüseyin Onay; Özgür Çoğulu; Ferda Özkınay; et al. (Galenos Yayincilik, 2021)
Objective:The aim of this study was to assess the quality of life (QoL) and psychological well-being in child and adolescent with disorders of sex development (DSD).Methods:Sixty-two cases, aged 2-18 years, who were followed by a multidisciplinary DSD team were included. All participants and their parents were requested the complete the Pediatric Quality Of Life Inventory (PedsQL) and the Strengths and Difficulties Questionnaire. The psychiatric diagnoses of the patients were evaluated according to Schedule for Affective Disorders and Schizophrenia for School-Age Children/Present and Lifetime Turkish Version.Results:There was no significant difference between the 46,XX DSD and 46,XY DSD groups for both child and parent in Total PedsQL score. In the subscale scores, the PedsQL Physical Functionality Score reported by children was significantly lower for the 46,XX DSD group than for the 46,XY DSD group (p=0.01). There was a psychiatric diagnosis in 25.8% of cases. The PedsQL School Functionality Score reported by children in the group with psychiatric diagnosis was significantly lower than the group without psychiatric diagnosis (p=0.018). In the group with psychiatric diagnosis, the PedsQL Total Score and the subscale scores (Emotional Functionality Score, Social Functionality Score, School Functionality) reported by parents were significantly lower than in parents of the group without psychiatric diagnosis.Conclusion:This study emphasized that psychiatric disorders in DSD patients negatively affect the QoL. Psychiatric support and counseling from a multidisciplinary team are very important for families affected by DSD.